A Physically Based Spatial Expansion Algorithm for Surface Air Temperature and Humidity - Hongbo Su; Jing Tian; Renhua Zhang; Shaohui Chen; Yongmin Yang; Yuan Rong; Sujuan Mi; Jianwei Qi (Advances in Meteorology)
An algorithm was developed to expand the surface air temperature and air humidity to a larger spatial domain, based on the fact that the variation of surface air temperature and air humidity is controlled jointly by the local turbulence and the horizontal advection. This study proposed an algorithm which considers the advective driving force outside the thermal balance system and the turbulent driving force and radiant driving force inside the thermal balance system. The surface air temperature is determined by a combination of the surface observations and the regional land surface temperature observed from a satellite. The average absolute difference of the algorithm is 0.65 degree and 0.31 mb, respectively, for surface air temperature and humidity expansion, which provides a promising approach to downscale the two surface meteorological variables.